2018
DOI: 10.1681/asn.2017080859
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association of the HLA-DR/DQ Locus with Childhood Steroid-Sensitive Nephrotic Syndrome in the Japanese Population

Abstract: Nephrotic syndrome is the most common cause of chronic glomerular disease in children. Most of these patients develop steroid-sensitive nephrotic syndrome (SSNS), but the loci conferring susceptibility to childhood SSNS are mainly unknown. We conducted a genome-wide association study (GWAS) in the Japanese population; 224 patients with childhood SSNS and 419 adult healthy controls were genotyped using the Affymetrix Japonica Array in the discovery stage. Imputation for six genes (, ,, , and) was conducted on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 52 publications
6
53
0
Order By: Relevance
“…Shown is the LD data for the lead HLA SNPs identified in previous GWAS of SSNS and this analysis, based on European reference data from the 1000 genome dataset. Note that the SNPs rs9273542 and rs2858317, identified in this analysis are in strong LD with rs4642516, identified by Jia et al 23 and with two markers, rs1063348 and rs28366266, identified by Debiec et al. 24 In contrast, the third, most telomeric marker identified by Debiec et al rs9348883 is only in weak LD with the other markers.…”
Section: Supplementary Figure 5 Manhattan Plot With Genotyped Markersupporting
confidence: 45%
“…Shown is the LD data for the lead HLA SNPs identified in previous GWAS of SSNS and this analysis, based on European reference data from the 1000 genome dataset. Note that the SNPs rs9273542 and rs2858317, identified in this analysis are in strong LD with rs4642516, identified by Jia et al 23 and with two markers, rs1063348 and rs28366266, identified by Debiec et al. 24 In contrast, the third, most telomeric marker identified by Debiec et al rs9348883 is only in weak LD with the other markers.…”
Section: Supplementary Figure 5 Manhattan Plot With Genotyped Markersupporting
confidence: 45%
“…Additionally, HLA-DRB1*04:05-DQB1*04:01, HLA-DRB1*08:02-DQB1*03:02, and HLA-DRB1*09:01-DQB1*03:03 haplotypes are associated with susceptibility to T1DM [ 29 ]. Recently, it has been reported that the HLA-DRB1*08:02, HLA-DQB1*03:02 alleles, and the HLA-DRB1*08:02-DQB1*03:02 haplotype is highly associated with steroid-sensitive nephrotic syndrome in Japanese children [ 30 ]. Although we had speculated that our patient would have HLA-DRB1*08:02-DQB1*03:02, she had HLA-DRB1*09:01/09:01 and DQB1*03:03/03:03.…”
Section: Discussionmentioning
confidence: 99%
“…Both the patient and her mother had specific HLA haplotypes that are highly associated with T1DM, but only the daughter developed MCNS. HLA-DRB1*09:01-DQB1*03:03-DPB1*02:01 and HLA-A*02:06-C*08:01-B*40:06-DRB1*09:01-DQB1*03:03 haplotypes have been reported to be associated with childhood steroid-sensitive nephrotic syndrome in Japan, so our patient might have either one of the two haplotypes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent genetic studies implicate variants in major histocompatibility complex, class II, DQ alpha 1 (HLA-DQA1), other major histocompatibility class II loci, and phospholipase C gamma 2 (PLCG2) as important risk factors for NS and further support the importance of defective B-cell functions in the pathogenesis of the disease. 1,3,4 Corticosteroid is the mainstay of treatment for NS, and the disease is classified as steroid-sensitive nephrotic syndrome (SSNS), frequent relapsing (FR), steroid dependent (SD), and steroid-resistant NS based on response to corticosteroid therapy. The reasons for variability in response to corticosteroid therapy in a disease in which dysregulation of immune cells is central to pathogenesis is largely unknown.…”
Section: See Clinical Investigation On Page 971mentioning
confidence: 99%